El teatro foro como estrategia preventiva para el consumo de alcohol en los estudiantes de noveno grado de educación básica paralelo b, de la unidad educativa del milenio Bernardo Valdivieso, 2019-2020 - Vegas Apolo, Jocelyn Nicole (2021)
The research work titled: “El Teatro Foro como estrategia preventiva para el consumo de alcohol en los estudiantes de noveno grado de Educación Básica paralelo B, de la Unidad Educativa del Milenio Bernardo Valdivieso, 2019-2020” had as general objective to propose forum theater as a preventive strategy for alcohol consumption in ninth grade students, section B, at Unidad Educativa del Milenio “Bernardo Valdivieso”.To develop the research, it was applied a non-experimental design, descriptive type with a sample of 30 students from 12 to 14 years old. Therefore, it was used the scientific, deductive, inductive, analytical, synthetic, historical, and statistical methods, on the other hand, the technique used for this research was the survey and as an instrument, it was used the consumption of alcohol attitude test. Hence, among the main results, it was determined that 67% of the investigated, presents a frankly favorable attitude towards alcohol consumption. It is concluded that facing the high percentage of students with a positive attitude towards alcohol consumption, the Theater-forum is a participatory and creative psychoeducational strategy for the prevention of alcohol consumption in teenagers.